A bibliometric analysis of immersive technology in museum exhibitions: exploring user experience - Li, Jingjing; Wider, Walton; Ochiai, Yoichi; Muhammad Ashraf, Fauzi (Frontiers Media SA, 2023)
Introduction: This study aims to comprehensively understand the existing literature on immersive technology in museum exhibitions, focusing on virtual reality (VR), augmented reality (AR), and the visitor experience. The research utilizes a bibliometric approach by examining a dataset of 722 articles with two main research objectives. Firstly, it seeks to analyze current trends in immersive technology literature, specifically emphasizing VR and the user experience in museum exhibitions through co-citation analysis. Secondly, it aims to identify emerging research trends using co-word analysis. Methods: The study employs a bibliometric approach, specifically co-citation and co-word analysis, to investigate trends and forecast emerging areas in the field, particularly the role of VR in the museum context. Results: The analysis reveals the presence of five interconnected thematic clusters in the literature. These clusters include (1) VR and AR-enhanced heritage tourism, (2) VR and AR-enabled virtual museums, (3) interactive digital art education in immersive environments, (4) immersive storytelling in virtual heritage spaces, and (5) mobile AR heritage revival. Discussion: The article highlights influential works within these areas, showcasing the historical evolution of the field and the current emphasis on utilizing VR to create immersive, educational, and engaging experiences for museum visitors. The findings indicate that research on VR applications for museum exhibitions has predominantly focused on profound game-driven experiences and interactive 3D heritage, resulting in improved visitor engagement and access to cultural content. The adoption of VR technology holds the potential to revolutionize user experiences within the cultural heritage sector and reshape the overall landscape of museums and exhibitions. By presenting these research trends, this study contributes to a deeper understanding of the vital role of VR in enhancing visitor experiences in museum settings. Furthermore, it paves the way for further exploration and innovation in immersive technology.